2004
DOI: 10.1038/sj.eye.6701471
|View full text |Cite
|
Sign up to set email alerts
|

Invasive and noninvasive uveal melanomas have different adhesive properties

Abstract: Aims To establish if invasive and noninvasive uveal melanomas have differences in expression of adhesion molecules, and whether their adhesive interactions with the extracellular matrix (ECM) and endothelium vary. Methods Cells from an invasive and noninvasive uveal melanoma cell line and hepatic and dermal microvascular endothelial cells were assessed by flow cytometry for adhesion molecule expression. Tumour cell adhesion to ECM substrates (collagens I and IV, fibronectin, laminin, and vitronectin) and endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…One early step is cell adhesion (through integrins at the cell surface) to ECM components. It was recently shown that a1, a2, and a3 integrins showed higher expression in uveal melanoma cells with invasive phenotype compared with noninvasive cells, and inhibition of these a integrins decreased binding to collagen IV, fibronectin, and laminin (Woodward et al. 2005).…”
Section: Resultsmentioning
confidence: 99%
“…One early step is cell adhesion (through integrins at the cell surface) to ECM components. It was recently shown that a1, a2, and a3 integrins showed higher expression in uveal melanoma cells with invasive phenotype compared with noninvasive cells, and inhibition of these a integrins decreased binding to collagen IV, fibronectin, and laminin (Woodward et al. 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Although uveal melanomas have been reported to express a range of adhesion molecules, including integrins and members of the immunoglobulin family [5,6,[35][36][37][38], little is known about how adhesion protein expression may influence the invasion process in this tumor type. Moreover, it is unclear whether the same mechanisms important in cutaneous melanoma are equally relevant in uveal melanoma, or whether different interactions are required [39]. We observed an increase in ITGA8 within the more invasive group of uveal cell lines, whereas expression of ITGA6 and ITGB8 was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Seftor et al [4] described the involvement of high expression of laminin 5 and several members of the matrix metalloproteinase family in uveal melanoma progression. Additionally, uveal melanomas have been found to express more integrins than normal uveal melanocytes or spindle cell tumors that have a less aggressive and invasive phenotype [5,6]. [8][9][10][11][12][13], as well as phenotypic characteristics of these tumors such as invasive ability [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, proteins encoded by ITGA7 and ITGA9 genes belong to the integrin alpha chain family. Changes in integrins expression have been reported during the malignant progression of many tumors, and much evidence exists implicating their involvement in CM metastasis (21). Malacards also implicates ITGA7 and ITGA9 in CM (eighth and third rank of gene-related diseases, respectively).…”
Section: Resultsmentioning
confidence: 99%